Increased Income Economy Farmers of Farmers Group Sihuik-kuik Village in Angkola Selatan District, South Tapanuli Regency - Harahap, Muharram Fajrin; Nurmi, Aisyah; Sipahutar, Luky Wahyu; Khairani (Journal of Saintech Transfer, 2018)
Activities carried out in May-June 2018 aim to be an additional source of income to the community. Poor economic conditions are a source of declining levels of public health and education. The main problems faced by farmer group partners and village heads are: (1) community income is inadequate, (2) lack of knowledge of how to raise quail and formulation of rations, (3) partner duties as monitoring activities. The specific target of the PKM program is to create a safer and more conducive environment as an implication of the transfer of quail breeding knowledge and good ration formulation to give birth to a viable pioneer youth group who want to work and partners as monitors are expected to become new innovators independently in their environment. The methods offered: (a) Socialization of mentoring programs raising quails as an effort to convince partners to follow them, (b) Preparation of social preconditions (c) Implementation of quail farming assistance programs supported by Farmer Group Partners and Village Heads with Universities (Faculty of Animal Husbandry, Muhammadiyah University of South Tapanuli) to ensure knowledge transfer goes well and, (d) Monitoring, evaluation and reporting. During the event the target partner has activities showed high enthusiasm, proactive conditions and discussion. Constraints arise when monitoring activities, allegedly due to the low motivation of group members, the capacity of the cage and quail transferred by the PKM Team is not enough as a fundamental motivation for members. This suspicion is reinforced by the information obtained in the field, that in general the self-help groups (Farmer / Youth / Organization / Individual Groups) in this village have been accustomed to "enjoying" social activities in the form of assistance from government and private institutions through various programs with sufficient budget big. This condition triggers "laziness" members in maintaining the transferred assets.